A COMPARISON OF THE LARYNGEAL TUBE WITH THE LARYNGEAL MASK AIRWAY DURING SPONTANEOUS VENTILATION IN PAEDIATRIC ANAESTHESIA. - Hj.Ghazali, Dr.Norhafidzah; Nik Mohamad, Prof.Madya Dr. Nik Abdullah; A, Mohd Nikman; O., Mazelan; M.Z, Rhendra Hardy (2005)

(untitled)
To compare between laryngeal tube(LT)versus laryngeal mask airway (LMA) in terms of ease of insertion, quality of ventilation, haemodynamic response and complications in spontaneously ventilated paediatric patients undergoing general anaesthesia.